Improving Learning Outcomes Materials on Earth's Rotation and Eclipses Through Demonstration Methods - Sri Suharti (CV. Rayyan Dwi Bharata, 2023)
This study aims to examine the extent to which the learning outcomes of grade IV students at SD Negri 2 Belikurip have increased after the application of the demonstration method to learning rotation and revolution of the earth and the occurrence of lunar and solar eclipses. This research is a Classroom Action Research (CAR). The subjects of this study were 11 fourth grade students at SD Negri 2 Belikurip. This research was conducted in 2 cycles, each cycle held 2 meetings. The first meeting explained the material using the demonstration method and the second meeting was to carry out tests. The results of this study concluded that with the demonstration method it can be concluded: (1) active learning reached 11 students or 100% with an average value of 92; (2) learning outcomes reached 11 students or 100% with an average value of 90.9; (3) The activity and learning outcomes reached 11 students or 100% with an average score of 91.5 or all of them were in the very good category (A).